978-623-09-6726-9 Manajemen Keuangan: Asuransi Dan Manajemen Risiko - Andi Sartika Juniarmita, Andi Sartika Juniarmita; Misrah, Misrah; Agus umar Gazali, Agus umar Gazali; Ris Akril Nurimansjah, Ris Akril Nurimansjah; Mustafa, Mustafa; Nurlaela, Nurlaela; Samsu Gaffar, Samsu Gaffar; Andi Aris Mattunruang, Andi Aris Mattunruang; Andi Tenri Uleng Akal, Andi Tenri Uleng Akal; Syamsul Bakhtiar Ass, Syamsul Bakhtiar Ass; Andi Muhammad Irwan, Andi Muhammad Irwan; Sarnawiah, Sarnawiah; Darnawati, Darnawati; Haeril, Haeril (Lajagoe Pustaka, 2023)
Buku